92 ADRENAL INSUFFICIENCY AS THE INITIAL PRESENTATION OF HIV DISEASE. (1st March 2007) - Sircar, P.; Godkar, D.; Balachandran, J.; Niranjan, S.
Abstract : Introduction: Endocrine deficiencies, particularly functional abnormalities of the hypothalamopituitary-adrenal axis, are common in patients with human immunodeficiency virus (HIV) disease. In most cases, adrenal insufficiency, although present, is not enough to cause clinical symptoms. Few cases have been reported where adrenal insufficiency was the only complaint, or even more rarely, the presenting complaint of a patient with HIV disease, without evidence of any superimposed opportunistic infections. We present such a rare case, as we encountered at our hospital. Case Report: A 31-year-old African American male with no significant past medical history presented to the emergency room with 2 to 3 days of severe weakness, dizziness, fatigue, and vomiting. He was found to be hypotensive (blood pressure 70/50 mm Hg), the hypotension being refractory to fluid resuscitation. The patient was also hyperkalemic (potassium 5.5 mEq/L). Baseline cortisol was 5.1 mg/dL; stimulated value at the end of 1 hour with 250 μg of cosyntropin was 8.7 mg/dL. Extensive workup for sepsis was negative, and so were CMV, Toxoplasma, and cryptococcal antibody titers. CD4 count was 6/μL, and antibody to HIV-1 virus was positive, with a viral load of 450, 000 copies/mL. The patient ultimately responded to stress doses of hydrocortisone(300 mg/d) during a hospital stay and was discharged on maintenance doses of 20 mg of hydrocortisone at am and 10 mg at pm. At 6 months of follow-up, the patient was doing well, and although it has not been possible to take him off steroids, he is currently on a maintenance dose of 10 mg at am and 5 mg at pm of hydrocortisone. Discussion: Various mechanisms have been proposed to explain the mechanism of adrenal insufficiency in HIV-positive individuals. More often than not, infective agents such as CMV, cryptococcus, human herpesvirus 8, and tuberculosis have been found to be the culprits. Many times, no definite etiology can be found, and such cases are usually attributed to HIV itself or some abnormal autoimmune process getting triggered in the face of generalized reduction in body immunity. Further research is needed to understand the true mechanism of adrenal insufficiency in such obscure cases. This rare case also serves as a reminder to clinicians to keep in mind the differential diagnosis of adrenal insufficiency as the presenting picture of acquired immune deficiency syndrome (AIDS), even when a background diagnosis of HIV positivity is absent.